1986
DOI: 10.1038/jcbfm.1986.128
|View full text |Cite
|
Sign up to set email alerts
|

Regional Studies of Blood—Brain Barrier Transport of Glucose and Leucine in Awake and Anesthetized Rats

Abstract: Summary: D-Glucose and L-leucine are transported across the blood-brain barrier (BBB) by two separate carrier-mediated facilitated diffusion mechanisms. In the awake rat there are regional differences in blood-to-brain glucose transport among the cerebral cortex, cerebellum, hippocampus, and striatum. To determine whether these are due to variations in the regional density or affinity of the glucose transporter moiety of brain capillaries or are secondary to regional tissue perfusion and capillary ar rangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
14
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…Weight gain was less in the KG group than in the other two groups, but there were no significant differences among diet groups. The physiological data were similar to those we previously reported in chloral hydrate-anesthetized rats (16,17,35).…”
Section: Effect Of Ketosis On Plasma ␤-Hb Concentrationsupporting
confidence: 90%
See 3 more Smart Citations
“…Weight gain was less in the KG group than in the other two groups, but there were no significant differences among diet groups. The physiological data were similar to those we previously reported in chloral hydrate-anesthetized rats (16,17,35).…”
Section: Effect Of Ketosis On Plasma ␤-Hb Concentrationsupporting
confidence: 90%
“…The trends in regional blood flows in the STD group showed that blood flow was highest in the cortex [1.1 (SD 0.1)] and brain stem (1.4 Ϯ 0.2) and lowest in the cerebellum [0.90 (SD 0.2)]. Regional blood flows measured in this study were comparable to those previously reported using the blood flow-indicator method (16,17,35,44).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Sev eral studies have concluded that the vascular vol ume of the cerebellum is from 10 to 60% higher than that in the cerebrum (see Table O. The methods used to measure vascular volume in these studies employed radiolabeled tracers such as e4C]inulin (LaManna and Harik, 1986), eH]sucrose (Picozzi et aI., 1985), 125I_serum albumin (Cremer and Seville, 1983;Pluta et aI., 1989), and/or 51C-Iabeled red blood cells (Johanson, 1980;Cremer and Seville, 1983;Pluta et aI., 1989). The important feature that these techniques have in common is that the tracer cerebellum and cerebrum.…”
mentioning
confidence: 99%